Short delay to initiate plasma exchange is the strongest predictor of outcome in severe attacks of NMO spectrum disorders. Issue 4 (13th October 2017) - Bonnan, Mickael; Valentino, Rudy; Debeugny, Stéphane; Merle, Harold; Fergé, Jean-Louis; Mehdaoui, Hossein; Cabre, Philippe
Abstract : Introduction: Severe attacks of neuromyelitis optica spectrum disorder (NMO-SD) are improved by plasma exchange (PLEX) given as an adjunctive therapy. Initial studies failed to demonstrate a delay of PLEX treatment influenced clinical outcome; however PLEX was always used late. We examine the clinical consequences of delay in PLEX initiation on severe optic neuritis and spinal cord attacks in NMO-SD. Methods: All of our patients who suffered attacks of NMO-SD, treated in our centre by PLEX, were retrospectively considered for inclusion. Primary outcome was defined as complete improvement. Secondary poor/good outcomes were respectively defined to be the higher/lower third of Delta-Expanded Disability Status Scale (EDSS) (late minus baseline EDSS). Delays from clinical onset to PLEX initiation were categorised for multivariate analysis. Results: Of the 60 patients included, NMO-SD criteria (2015) were fulfilled in 92%. One hundred and fifteen attacks were included and received PLEX with a median of 7 days (0–54) after clinical onset. The probability to regain complete improvement continuously decreased from 50% for PLEX given at day 0 to 1%–5% after day 20. Through multivariate analysis, the baseline impairment and PLEX delay were associated with the probability to complete improvement (OR 5.3; 95% CI 1.8 to 15.9). Reducing the PLEX delay also influenced the good secondary outcome but not the poor secondary outcome. Conclusions: These results confirm an improved clinical benefit of early initiation of PLEX during severe attacks of NMO-SD. Perceiving PLEX as a rescue therapy only after steroid failure could be deleterious.